2015
DOI: 10.3892/ijo.2015.3187
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33b inhibits lung adenocarcinoma cell growth, invasion, and epithelial-mesenchymal transition by suppressing Wnt/β-catenin/ZEB1 signaling

Abstract: Altered expression of microRNA (miRNA) is associated with lung carcinogenesis and metastasis. Our previous study of lung cancer miRNAs using the gene chip assay demonstrated altered miR-33b expression in lung adenocarcinoma. The present study further investigated miR-33b expression, function, and gene regulation in lung cancer cells in vitro and in nude mouse xenografts. Our data showed that the level of miR-33b expression was dramatically decreased in lung adenocarcinoma cell lines and tissues and that the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 55 publications
4
63
1
Order By: Relevance
“…44 Meanwhile, it was demonstrated that miR-33b inhibited cells growth, invasion and EMT by suppressing Wnt/β-catenin/ZEB1 signaling in lung adenocarcinoma. 45 In this study, we found that lower expression levels of E-cadherin and higher expression levels of Vimentin were detected in the cells that underwent EMT triggered by miR-218 inhibition. Ectopic expression of miR-218 decreased the invasive capacity of lung cancer cells.…”
Section: Discussionmentioning
confidence: 56%
“…44 Meanwhile, it was demonstrated that miR-33b inhibited cells growth, invasion and EMT by suppressing Wnt/β-catenin/ZEB1 signaling in lung adenocarcinoma. 45 In this study, we found that lower expression levels of E-cadherin and higher expression levels of Vimentin were detected in the cells that underwent EMT triggered by miR-218 inhibition. Ectopic expression of miR-218 decreased the invasive capacity of lung cancer cells.…”
Section: Discussionmentioning
confidence: 56%
“…The Wnt/ β -catenin signaling pathway plays an important role in the development of EMT and cancer metastasis [12]. Thus we further determine the β -catenin protein level in cell nucleus by using western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that overexpression of Wnt signaling pathway is involved in metastasis of lung cancer [12, 20]. Wnt/ β -catenin pathway can control cell proliferation by regulating the expression of cell cycle-related gene including c-Myc and modulate EMT by downregulating E-cadherin and upregulating N-cadherin [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…In other malignant tumors, many reports state that miRNAs can influence tumor invasion and metastasis by participating in the EMT process [2226]. In ovarian cancer, RhoC overexpression promotes EMT, invasion, and metastasis, and RhoC knockout reverses the promoter role of vascular endothelial growth factor (VEGF) and transforming growth factor (TGF) in EMT [16].…”
Section: Discussionmentioning
confidence: 99%